Pengaruh Penggunaan Metode Mengajar Bervariasi Terhadap Prestasi Belajar Siswa Dalam Mata Pelajaran PAI Di SMK Ciledug Al-Musaddadiyah Garut - Raito, Raito; Sarita, Dede (MASAGI : Jurnal Pendidikan Agama Islam, 2022)
Academic achievement remains a significant issue due to several factors: lack of student engagement with the material presented, indifference among students, and passive attitudes in the classroom. Therefore, utilizing a variety of teaching methods is a viable solution to address these student-related problems. This study aims to describe the influence of using diverse teaching methods in Islamic Religious Education (IRE) on students' academic performance. The research adopts a descriptive quantitative approach. Data collection methods include observation, document studies, and questionnaires distributed to 20 students who served as the sample for this study. Data analysis was conducted using statistical methods. The findings indicate that the average effectiveness of varied teaching methods is 4.00, which falls within the interval of 4.01-5.00, categorized as "Very Good." This suggests that the effectiveness of teaching has improved following the implementation of diverse teaching methods in the learning process. In terms of academic performance in IRE subjects, students achieved an average score of 4.09, also within the interval of 4.01-5.00, categorized as "Very Good." This demonstrates that the use of varied teaching methods is an appropriate solution to enhance student academic achievement. Statistical analysis confirms that there is a significant influence of using varied teaching methods in IRE on students' academic performance, accounting for 47.59% of the improvement, while other variables not examined in this study contribute to 52.40% of the influence on students' academic performance. Keywords: Diverse Teaching Methods, Student Academic Achievement, Islamic Religious Education